Nāmūdhaj Ta'allum al-Khaṭ fī Mahārah al-Kitābah fī al-Ma'had al-'Aṣrī Dār al-Salām Kūntūr al-Sābi' Kālīandā Lāmbūng al-Janūbiyyah: The Teaching Model of Calligraphy in Writing Skills at Pondok Modern Darussalam Gontor 7 Kalianda South Lampung - Alif Cahya Setiyadi; Afin Al Aufi; Pafi Rahmatullah Al Gifari; Jalaluddin (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
Calligraphy at Pondok Modern Darussalam Gontor 7 Kalianda is a mandatory and extracurricular subject that teaches writing Arabic letters according to calligraphy (khat) rules. The lesson aims to train students from an early age to write correctly and adequately, preventing errors in reading and understanding texts. This extracurricular activity is also expected to improve students' writing skills through the Hamidi method in pesantren education. CalligraphyCalligraphy is an art form that holds high aesthetic and spiritual value in Islamic culture and can be an effective tool in Arabic language education. The research methodology used in this study includes: 1) The type of research is qualitative research, 2) The subjects of this study are calligraphy teachers and students of Darussalam Gontor 7 Kalianda, 3) Data collection using observation, interview, and documentation techniques, 4) Analytical techniques using qualitative descriptive analysis techniques. The results show that the structured and continuous implementation of the calligraphy learning model significantly enhances students' writing skills regarding the beauty of the writing and the accuracy of language usage. This model also positively impacts students' motivation and interest in learning. Therefore, the calligraphy learning model is recommended to be integrated into the Arabic language curriculum to improve maharah kitabah competencies. Keywords: Calligraphy, Learning Model, Writing Skills